ISOLASI DAN UJI POTENSI ISOLAT BAKTERI PELARUT FOSFAT DAN BAKTERI PENGHASIL HORMON IAA (Indole Acetic Acid) TERHADAP PERTUMBUHAN KEDELAI (Glycine max L.) PADA TANAH KUNING - Dessy Merry Silitonga; Nunuk Priyani; Isnaini Nurwahyuni (Saintia Biologi, 2013)
Biofertilizer is a safe alternative fertilizer instead of various chemical fertilizers for increasing plant productivity which can minimize the ecological damage. There are plant symbiotic-soil bacteria which can solubilize phosphate or produce IAA. The objectives of this research are to determine the best soil bacteria in producing IAA or solubilizing phosphate and to know their roles in promoting plant growth in unfertile soil. As many as 8 isolates of phosphate solubilizing bacteria and 5 isolates of IAA producing bacteria were found. Among those isolates, there were 2 potential isolates (P2 & P4) that were able to solubilize phosphate and 1 potential isolate (I3) that was able to produce IAA. Isolate P4 produced holozone as wide as 1.45 cm and isolate P2 was 1.3 cm. Meanwhile, isolate I3 produced the highest concentration of IAA compared to the other isolates, that was 33.3 ppm. These isolates were applicated further on unfertile soil (yellow soil) as a medium for soybean growth. Soybeans have been grown for 10 weeks to observe the effect of those potential isolates on plant growth and productivity. The result showed that application of isolate I3 was able to promote plant growth and increase plant productivity better than the other isolates as well as controls (fertile and unfertile soil). It promoted the soybean growth such as plant height was 58,8 cm; plant fresh weight was 3.5 g; plant dry weight was 1.55; pod fresh weight was 1.23; pod dry weight was 1.03; the amount of the pod was 3 and the number of the seed was 7. Keywords : Phosphate solubilizing bacteria, IAA producing bacteria, biofertilizer, soybean.